1995
DOI: 10.1177/000348949510400605
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Regional Lymph Node Metastasis from Laryngeal Carcinoma

Abstract: A series of 103 cases of laryngeal carcinoma subjected either to a unilateral or to a bilateral comprehensive neck dissection was reviewed with reference to risk factors influencing regional lymph node metastasis. The sensitivity of clinical examination was only 67.4%, while the specificity was 88.3%. Most metastases were in the upper and middle jugular chain of nodes (levels 2 and 3). Only patients with positive nodes at levels 2, 3, and/or 4 had histologically positive nodes at levels 1 or 5. Selected demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 19 publications
0
23
0
4
Order By: Relevance
“…The incidence of neck-lymph node metastasis in glottic cancers is below 10%, while it ranges between 10-50% in supraglottic cancers. [16][17][18] Raitiola et al demonstrated that both regions showed differences in their T stages, and stated that supraglottic cancers had significantly higher T stages. In this study, glottic, and supraglottic localizations were observed in 53%, and 47% of the patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of neck-lymph node metastasis in glottic cancers is below 10%, while it ranges between 10-50% in supraglottic cancers. [16][17][18] Raitiola et al demonstrated that both regions showed differences in their T stages, and stated that supraglottic cancers had significantly higher T stages. In this study, glottic, and supraglottic localizations were observed in 53%, and 47% of the patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…6,8 Glottik kanserlerde servikal metastaz oranları %10'un altında iken supraglottik kanserlerde bu oranın %20 -50 arasında değiştiği bildirilmiştir. 10,11,14 Zengin lenfatik vaskülarizasyondan dolayı ve bazen de kötü diferansiasyona bağlı olarak supraglottik kanserler, erken evrelerde bile sıklıkla klinik olarak tespit edilebilen bölgesel boyun metastazıyla karşımıza gelebilmektedir.…”
Section: Giannini Ve Arkadaşlarınınunclassified
“…17 Bizim çalışmamızdaki 108 supraglottik kanserli vakanın 49'unda (%45.3) ipsilateral servikal metastaz, 25 vakada (%23) ise occult metastaz saptandı. Kowalski ve arkadaşları, 6 yaptığı çalışmada, transglottik tümörlerde servikal metastaz oranını %41 olarak rapor etmişlerdir. Baş-ka bir çalışmada, transglottik tümörlerde servikal metastaz oranı %32 olarak bulunmuş ve 4 cm'den büyük transglottik tümörlerde ise %55 oranında servikal metastaz bildirilmiştir.…”
Section: Giannini Ve Arkadaşlarınınunclassified
“…This basic knowledge provides a basis for planning of neck dissection in relation to the primary tumor. Lateral neck dissection (SND II-IV) has been used widely in the past twenty years for management of the neck in clinically N0 laryngeal cancer because it has been demonstrated that metastases of laryngeal cancer usually occurs in these levels and levels I and V are rarely involved (Robbins, 2002, Kowalski, 1995, Jones, 1994. SND II-IV is very effective in treating occult metastases and in a previous study from the author of this chapter's department, it has been demonstrated that a neck recurrence rate as low as 1.7% can be achieved after SND II-IV (Erisen, 2001).…”
Section: Selective Neck Dissection For Laryngeal Cancermentioning
confidence: 99%